DATA COLLECTION: AN EXPERIENCE FOR TEACHING AND FOR RESEARCH - Ana Lúcia Cardoso Kirchhof; Tânia Solange Bosi de Souza Magnago; Silviamar Camponogara; Francine Cassol Prestes; Raquel Soares Kirchhof (Universidade Federal do Paraná, 2009)
Research has been a strong ally to the improvement of health care quality by providing reflection concerningdifferent practices. The objective of this text is to demonstrate the importance of the participation of academics in research,providing both by living with the resulting questions of professional relationships and the aspects related to the executionof an investigative project. In order to do so, the capacitation of interviewers, the challenges of data collection, and thebenefits earned by the experience of being an academic/researcher are detailed. This report shows that the theoretical-practical experiences achieved during the undergraduate curriculum create a differential of knowledge for academics andprofessors, if complemented with research experiences.